1988
DOI: 10.1113/jphysiol.1988.sp017267
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotide‐ and inositol 1,4,5‐trisphosphate‐induced calcium release in rabbit main pulmonary artery.

Abstract: 1. The effects of activation of guanine nucleotide‐binding protein (G protein) by guanine nucleotides or sodium fluoride on the release of intracellular Ca2+ and on tension development were determined in chemically skinned strips of rabbit main pulmonary arteries (MPA). Ca2+ movements were monitored with Fura‐2, as the change in free Ca2+ concentration in the bath medium surrounding the skinned MPA. 2. Sodium fluoride or non‐hydrolysable analogues of GTP, guanosine 5'‐[gamma‐thio]triphosphate (GTP gamma S) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…(2) In smooth muscle, pharmacomechanical Ca2+ release is a major mechanism of excitation-contraction coupling (Somlyo, 1985). It is mediated by activation of the phospholipase C-inositol trisphosphate (1P,) cascade, coupled to receptors by G-proteins, and inhibitors of phospholipase C (neomycin) and of IP3 (heparin) block the release of intracellular Ca2+ induced by agonists, but not by caffeine (Kobayashi, Somlyo & Somlyo, 1988;Kobayashi, Kitazawa, Somlyo & Somlyo, 1989;Yamamoto, Kanaide & Nakamura, 1990). The present study showed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In smooth muscle, pharmacomechanical Ca2+ release is a major mechanism of excitation-contraction coupling (Somlyo, 1985). It is mediated by activation of the phospholipase C-inositol trisphosphate (1P,) cascade, coupled to receptors by G-proteins, and inhibitors of phospholipase C (neomycin) and of IP3 (heparin) block the release of intracellular Ca2+ induced by agonists, but not by caffeine (Kobayashi, Somlyo & Somlyo, 1988;Kobayashi, Kitazawa, Somlyo & Somlyo, 1989;Yamamoto, Kanaide & Nakamura, 1990). The present study showed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the depleting action of GTPyS was completely prevented by heparin (5 mg/ml), an obvious explanation is that GTPyS acts by increasing InsP3 production and that this occurs because GTPyS binds to a G-protein associated with PLC in the cell and in this way accelerates its activity. Thus GTPyS in jejunal cells does not seem to have any direct depleting action on the Ca store, as it does in permeabilized pulmonary artery smooth muscle strips (Kobayashi, Somlyo & Somlyo, 1988b).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GTPrS was preserved after blockade of IP3 receptors with heparin (14), elimination of Ca" stores with A23187 (15) or reduction of the stored Ca 21 with caffeine. Therefore, it is unlikely to be due to such an action of GTPrS on Ca2+ stores through an IP3 independent process as described for the pulmonary arteri al smooth muscle (12). The fact that GTPrS can cause depletion of Ca" stores exclusively through IP3 is demon strated by using Ca2+-activated K+ current as an indica for showing Ca 21 stores available for release in single volt age-clamped cells from rabbit jejunum (4).…”
Section: Discussionmentioning
confidence: 99%
“…The difference may arise by a slow diffusion of GTPrS from the patch pipette into the cell. In chemi cally-skinned arterial muscle strips, the GTPrS-induced Ca 2+ release has been reported to involve both IP3-de pendent and independent mechanisms (12).…”
mentioning
confidence: 99%